Massively parallel reporter assays and mouse transgenic assays provide correlated and complementary information about neuronal enhancer activity - Michael Kosicki; Dianne Laboy Cintrón; Pia Keukeleire; Max Schubach; Nicholas F. Page; Ilias Georgakopoulos-Soares; Jennifer A. Akiyama; Ingrid Plajzer-Frick; Catherine S. Novak; Momoe Kato; Riana D. Hunter; Kianna von Maydell; et al. (Nature Communications)
Abstract High-throughput massively parallel reporter assays (MPRAs) and phenotype-rich in vivo transgenic mouse assays are two potentially complementary ways to study the impact of noncoding variants associated with psychiatric diseases. Here, we investigate the utility of combining these assays. Specifically, we carry out an MPRA in induced human neurons on over 50,000 sequences derived from fetal neuronal ATAC-seq datasets and enhancers validated in mouse assays. We also test the impact of over 20,000 variants, including synthetic mutations and 167 common variants associated with psychiatric disorders. We find a strong and specific correlation between MPRA and mouse neuronal enhancer activity. Four out of five tested variants with significant MPRA effects affected neuronal enhancer activity in mouse embryos. Mouse assays also reveal pleiotropic variant effects that could not be observed in MPRA. Our work provides a catalog of functional neuronal enhancers and variant effects and highlights the effectiveness of combining MPRAs and mouse transgenic assays.